A 3D printed lightweight high-strength low-carbon cement-based material and preparation method thereof

Through 3D printing technology, a lightweight, high-strength, low-carb cement-based material is prepared by the synergistic effect of modified sintered mullite, mineral blends, coral aggregates, zeolites, cement, clay and nano-spark water, which solves the problem of insufficient compressive performance and lightweight strength reduction in traditional cement-based materials, and achieves the goal of efficient compressive performance improvement and low-carbon environmental protection.

CN119320261BActive Publication Date: 2025-04-08CHINA CONSTR WESTERN CONSTR NORTH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411879402.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-08
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Traditional cement-based materials lack compressive resistance in high-rise buildings and large-span structures, and lightweight treatment often leads to a decrease in material strength, making it difficult to meet the needs of lightweight and high strength at the same time.

Method used

Using 3D printing technology, a lightweight, high-strength, low-carbohydrate cement-based material is prepared by modifying the synergy of sintered mullite, mineral blends, coral aggregates, zeolites, cement, clay and nano-sparkled water. Modified sintered mullite is modified by wrapping hydrophobic materials to improve the waterproofing performance and strength of the aggregate; coral aggregates and zeolites provide physical enhancement effects; nano-sparkle water improves the microstructure of the material, fills pores and inhibits cracks.

Benefits of technology

It has achieved the realization of significantly improving the compressive strength and durability while maintaining the lightweight material, reducing its dependence on traditional sand and gravel resources, reducing carbon emissions, and realizing low-carbon and environmentally friendly building materials production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of building materials, and specifically discloses a 3D printed lightweight high-strength low-carbon cement-based material and a preparation method thereof. A 3D printed lightweight high-strength low-carbon cement-based material, comprising the following raw materials by weight: 50-70 parts of modified sintered mullite, 5-8 parts of mineral admixture, 8-12 parts of coral aggregate, 8-10 parts of zeolite, 60-80 parts of cement, 10-20 parts of clay, and 60-75 parts of nano bubble water, wherein the modified sintered mullite is obtained by wrapping and modifying with a hydrophobic material; its preparation method is as follows: after weighing each raw material, the modified sintered mullite, mineral admixture, coral aggregate, zeolite, cement and clay are stirred and mixed to obtain a mixture; nano bubble water is added to the mixture for secondary stirring to obtain a 3D printed lightweight high-strength low-carbon cement-based material. The composition of the present application can be used for preparing cement-based materials using 3D printing technology, and it has the advantages of high compressive strength and good durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and more specifically, to a 3D printed lightweight, high-strength, low-carbon cement-based material and a preparation method thereof. Background Art

[0002] With the vigorous development of the global construction industry and the emphasis on sustainable development, the requirements for the performance of building materials are becoming increasingly stringent. Especially at a time when energy conservation, emission reduction and green environmental protection have become the consensus of the industry, lightweight, high-strength and low-carbon building materials have become the focus of scientific research and industry. Traditional cement-based materials, as the cornerstone of the construction field, have been widely used in various building structures, but their own limitations are becoming increasingly prominent.

[0003] In terms of compressive strength, although traditional cement-based materials can meet general construction needs, their compressive performance is often insufficient when faced with high-performance application scenarios such as high-rise buildings and large-span structures. Although compressive strength can be improved to a certain extent by adding reinforcing materials such as fibers and polymers, these methods are often accompanied by increased costs and increased process complexity, and the effect is limited, making it difficult to simultaneously meet the needs of lightweighting.

[0004] Lightweighting is another important direction to improve the performance of building materials. By adding lightweight aggregates such as perlite and ceramsite, the weight of the material can be reduced to a certain extent. However, this simple lightweighting treatment often leads to the sacrifice of material strength, making lightness and high strength a pair of irreconcilable contradictions. How to keep the material lightweight while not reducing or even improving its compressive strength is an urgent problem to be solved in the current field of building materials.

[0005] Therefore, developing a 3D printed lightweight, high-strength, low-carbon cement-based material that can solve the above problems at the same time is of great significance to promoting the sustainable development of the construction industry. Summary of the invention

[0006] In order to achieve lightweight 3D printed cement-based materials while improving compressive strength, the present application provides a 3D printed lightweight, high-strength, low-carbon cement-based material and a preparation method thereof.

[0007] This application provides a 3D printed lightweight, high-strength, low-carbon cement-based material, which adopts the following technical solution:

[0008] In a first aspect, a 3D printed lightweight, high-strength, low-carbon cement-based material comprises the following raw materials in parts by weight:

[0009] 50-70 parts of modified sintered mullite, 5-8 parts of mineral admixture, 8-12 parts of coral aggregate, 8-10 parts of zeolite, 60-80 parts of cement, 10-20 parts of clay, and 60-75 parts of nano bubble water. The modified sintered mullite is obtained by being wrapped and modified by a hydrophobic material.

[0010] By adopting the above technical solution, lightweight and efficient modified sintered mullite is used as the main skeleton. This material has a low density while ensuring high strength, effectively reducing the deadweight load of the building structure. Combined with the synergistic effect of modified sintered mullite, mineral admixtures, coral aggregate and zeolite, the chemical reactivity and micro-aggregate effect of mineral admixtures, and the physical reinforcement of coral aggregate and zeolite, the compressive strength and durability of the material are significantly improved. The added coral aggregate and zeolite are both natural materials. Their use reduces the dependence on traditional sand and gravel resources, helps to reduce carbon emissions in the mining process, and achieves low carbon. The addition of clay and nano bubble water improves the workability and fluidity of the material, promotes the hydration reaction of cement, and together with cement, builds a denser hardened layer, greatly improving the overall strength of the mixture. Nano bubble water, with its unique micro bubble structure and high surface tension characteristics, can penetrate deeply into the microstructure of cement-based materials to form a stable foam system. These foams effectively fill pores and inhibit cracks during the hardening process, further enhancing the compressive performance of the material.

[0011] Optionally, the preparation of the modified sintered mullite specifically comprises the following steps:

[0012] (1) Add ethanol and water to ethyl orthosilicate and stir to mix, add ammonium hydroxide and stir to disperse, add tert-butyl glycidyl carbonate and mix, keep in a water bath at 30°C and allow to react for 18-24 hours;

[0013] (2) Add acrylic resin into xylene, heat and stir until the acrylic resin is dissolved, add the sol prepared in step (1), continue stirring and mixing, and obtain a mixed solution. Add sintered mullite into the mixed solution and immerse it. Filter, remove, dry and solidify at 60-80°C to obtain modified sintered mullite.

[0014] By adopting the above technical solution, although the porous material reduces the structural load and thus reduces the quality of cement, it is also easy to absorb water and other liquids due to its porous structure. These liquids move or accumulate inside the material, which may cause the material to expand, shrink or corrode. For example, the accumulation of water in the porous material may cause volume changes, thereby generating internal stress, which may cause the material to crack or damage. Therefore, hydrophobic materials are used to wrap and modify the sintered mullite to avoid the damage of water and alkaline components in cement to the aggregate structure.

[0015] In the process of preparing modified sintered mullite, tetraethyl orthosilicate (TEOS) is added to a mixed solution of ethanol and ammonium hydroxide. Ethanol, as a solvent, helps to disperse tetraethyl orthosilicate; while ammonium hydroxide, as a catalyst, promotes the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After sufficient stirring, tetraethyl orthosilicate is evenly dispersed in the mixed solution and gradually forms a sol. Next, tertiary carbon structure of tert-butyl carbonate is added to increase the steric hindrance of the gel and improve the waterproof performance of the hydrogel. Further, tert-butyl carbonate can react with the carboxyl group in the acrylic resin, thereby grafting into the acrylic polymer segment, forming an organic-inorganic composite layer on the surface of the mullite, giving the mullite better waterproof performance. The modified sintered mullite is separated by filtration and placed at 60-80°C for drying and curing treatment to completely remove the residual solvent and moisture in the aggregate, promote the close bonding between the sediment layer and the aggregate, and further enhance its hydrophobicity, thereby avoiding damage to the aggregate by other liquids such as water, enhancing the performance of the aggregate, and thus improving the durability of the prepared cement-based material.

[0016] Preferably, the acrylic resin is a thermosetting acrylic resin.

[0017] Optionally, the weight ratio of tetraethyl orthosilicate, tert-butyl glycidyl carbonate, acrylic resin and sintered mullite is 3-4:0.8:4.5-6.2:2.

[0018] Optionally, in step (2), after the sintered mullite is added to the mixed solution, 2-butanone is added dropwise, and the weight ratio of the 2-butanone to the sintered mullite is 0.2-0.4:1.

[0019] By adopting the above technical solution, 2-butanone is added as a non-solvent during impregnation. The addition of 2-butanone changes the solvent environment in the solution, prompting the acrylic resin and silica gel to deposit and solidify on the surface of the sintered mullite, further enhancing the modification of the sintered mullite by the encapsulating material.

[0020] Optionally, the particle size of the sintered mullite is between 2-3 mm.

[0021] By adopting the above technical solution and controlling the aggregate particle size within an appropriate range, the mullite particles can provide sufficient strength support and maintain good interface bonding force, thereby enhancing the compressive strength of the material. At the same time, during the modification process, the modified material can better wrap the sintered mullite, achieve uniform wrapping and uniform particle distribution, reduce stress concentration points inside the material, and thus improve the compressive strength and durability of the material.

[0022] Optionally, the mineral admixture is obtained by mixing microsilica powder and diatomaceous earth in any weight ratio.

[0023] By adopting the above technical solution, the addition of microsilica powder and diatomaceous earth not only improves the compressive strength of the material, but also improves the fluidity of the material, making it have better fluidity, ensuring the uniformity and constructability of the material during 3D printing. In addition, microsilica powder can also react with calcium hydroxide in cement to form hydrated calcium silicate gel. The formation of this gel helps to enhance the gelling properties of concrete and further improve the durability and resistance to chemical erosion of concrete. Diatomaceous earth has a certain structural stability and strength. While maintaining strength, it reduces the density of the material and further reduces the weight of the material.

[0024] Optionally, the raw materials further include 10-15 parts of water-based epoxy resin.

[0025] By adopting the above technical solution, water-based epoxy resin can further strengthen the bonding effect between aggregate and cement matrix, and can react with acrylic resin on the surface of aggregate to form a more solid and stable network structure, effectively disperse and transfer stress, prevent damage caused by stress concentration, and further improve the compressive strength of cement-based materials.

[0026] In the second aspect, the present application provides a method for preparing a 3D printed lightweight, high-strength, low-carbon cement-based material, using the following technical solution:

[0027] A method for preparing a 3D printed lightweight, high-strength, low-carbon cement-based material comprises the following steps:

[0028] (1) After weighing the raw materials, the modified sintered mullite, mineral admixture, coral aggregate, zeolite, cement and clay are stirred and mixed to obtain a mixture;

[0029] (2) Adding nanobubble water to the mixture and performing secondary stirring to obtain a 3D printed lightweight, high-strength, low-carbon cement-based material.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. This application uses modified sintered mullite as the main skeleton. This material has a low density while ensuring high strength, effectively reducing the deadweight load of cement-based materials and improving the economy and sustainability of the building. Combined with natural materials such as coral aggregates and zeolites, it reduces dependence on traditional sand and gravel resources, reduces carbon emissions during the mining process, and realizes the production of low-carbon and environmentally friendly building materials.

[0032] 2. In this application, the hydrophobic wrapping treatment of the modified sintered mullite effectively prevents the damage to the aggregate structure by moisture and alkaline components in cement, thereby improving the durability of the material. The synergistic effect of mineral admixtures, coral aggregates and zeolites significantly improves the compressive strength of the material. The addition of nano bubble water further improves the microstructure of the material, fills pores, inhibits the generation of cracks, and strengthens the compressive properties of the material. Controlling the particle size of the sintered mullite between 2-3 mm not only provides sufficient strength support, but also ensures that the modified material can evenly wrap the aggregate, thereby improving the overall uniformity and compressive strength of the material.

[0033] 3. The addition of water-based epoxy resin in this application not only strengthens the bonding effect between aggregate and cement matrix, but also reacts with acrylic resin on the surface of aggregate to form a network structure, effectively disperses and transfers stress, prevents damage caused by stress concentration, and further improves the compressive strength and durability of cement-based materials. DETAILED DESCRIPTION

[0034] The present application is further described in detail below with reference to the embodiments.

[0035] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0036] Acrylic resin was purchased from Shanghai Jiushi Chemical Co., Ltd., model BR-73; sintered mullite was purchased from Jiangsu Yannai New Material Technology Co., Ltd., model SJ-M45, volume density ≥ 2.4 g / cm 3 ; Water-based epoxy resin was purchased from Guangzhou Taili Chemical Co., Ltd., model CYDW100, epoxy equivalent 190; cement is silicate cement purchased from Lingshou County Qianfu Mineral Products Processing Plant, strength grade 32.5.

[0037] Preparation Example

[0038] Preparation Example 1

[0039] A modified sintered mullite, the preparation of which comprises the following steps:

[0040] (1) Take 120 kg of ethyl orthosilicate, add 50 kg of ethanol and 30 kg of water, stir and mix, add 2 kg of ammonium hydroxide, stir and disperse thoroughly, add 64 kg of tert-butyl glycidyl carbonate, mix and heat in a water bath at 30°C for 22 hours to form a sol;

[0041] (2) 212 kg of acrylic resin is placed in xylene, heated to 130°C in an oil bath, stirred at a rate of 300 r / min until the acrylic resin is dissolved, the sol prepared in step (1) is added and stirred to obtain a mixed solution, 80 kg of sintered mullite is placed in the mixed solution and immersed for 60 minutes, filtered, removed, dried and solidified at 80°C to obtain modified sintered mullite. Xylene is used as a solvent, and the amount added is based on the ability to fully dissolve the raw materials. The particle size of the sintered mullite is 2-3 mm.

[0042] Preparation Example 2

[0043] A modified sintered mullite, the preparation of which comprises the following steps:

[0044] (1) Take 160 kg of ethyl orthosilicate, add 50 kg of ethanol and 30 kg of water, stir and mix, add 2 kg of ammonium hydroxide, stir and disperse thoroughly, add 64 kg of tert-butyl glycidyl carbonate, mix and heat in a water bath at 30°C for 18 hours to form a sol;

[0045] (2) 248 kg of acrylic resin was placed in xylene, heated to 130°C in an oil bath, stirred at a rate of 300 r / min until the acrylic resin was dissolved, the sol prepared in step (1) was added and continued to be stirred and mixed to obtain a mixed solution, 80 kg of sintered mullite was placed in the mixed solution and immersed for 60 minutes, filtered, removed, dried and solidified at 80°C to obtain modified sintered mullite. Xylene was used as a solvent, and the amount added was based on the ability to fully dissolve the raw materials. The particle size of the sintered mullite was 2-3 mm.

[0046] Preparation Example 3

[0047] A modified sintered mullite, the preparation of which comprises the following steps:

[0048] (1) Take 140 kg of ethyl orthosilicate, add 50 kg of ethanol and 30 kg of water, stir and mix, add 2 kg of ammonium hydroxide, stir and disperse thoroughly, add 64 kg of tert-butyl glycidyl carbonate, mix and heat in a water bath at 30°C for 24 hours to form a sol;

[0049] (2) 180 kg of acrylic resin is placed in xylene, heated to 130° C. in an oil bath, stirred at a rate of 300 r / min until the acrylic resin is dissolved, the sol prepared in step (1) is added and stirred to obtain a mixed solution, 80 kg of sintered mullite is placed in the mixed solution and immersed for 60 min, filtered, removed, dried and solidified at 80° C. to obtain modified sintered mullite. Xylene is used as a solvent, and the amount added is based on the amount that can fully dissolve the raw materials. The particle size of the sintered mullite is 2-3 mm.

[0050] Preparation Example 4

[0051] A modified sintered mullite, which is different from Preparation Example 1 in that 8 kg of 2-butanone is added dropwise after the sintered mullite is put into the mixed solution, specifically comprising the following steps:

[0052] (1) Take 120 kg of ethyl orthosilicate, add 50 kg of ethanol and 30 kg of water, stir and mix, add 2 kg of ammonium hydroxide, stir and disperse thoroughly, add 64 kg of tert-butyl glycidyl carbonate, mix and heat in a water bath at 30°C for 22 hours to form a sol;

[0053] (2) 212 kg of acrylic resin is placed in xylene, heated to 130°C in an oil bath, stirred at a rate of 300 r / min until the acrylic resin is dissolved, the sol prepared in step (1) is added and continued to be stirred and mixed to obtain a mixed solution, 80 kg of sintered mullite is placed in the mixed solution, 2-butanone is added while stirring, and then the mixture is allowed to stand for 60 minutes, filtered, removed, and dried and solidified at 80°C to obtain modified sintered mullite. Xylene is used as a solvent, and the amount added is based on the amount that can fully dissolve the raw materials. The particle size of the sintered mullite is 2-3 mm.

[0054] Preparation Example 5

[0055] A modified sintered mullite is different from Preparation Example 1 in that in this Preparation Example, 12 kg of 2-butanone is added dropwise after the sintered mullite is put into the mixed liquid.

[0056] Preparation Example 5

[0057] A modified sintered mullite is different from Preparation Example 1 in that in this Preparation Example, 16 kg of 2-butanone is added dropwise after the sintered mullite is put into the mixed liquid.

[0058] Preparation Example 6

[0059] A modified sintered mullite, which is different from Preparation Example 1 in that the sintered mullite used in this Preparation Example has a particle size of 3-4 mm.

[0060] Preparation Example 7

[0061] A modified sintered mullite, which is different from Preparation Example 1 in that the sintered mullite used in this Preparation Example has a particle size of 0.5-1 mm.

[0062] Comparative Preparation Example 1

[0063] A modified sintered mullite, the preparation of which comprises the following steps:

[0064] (1) Take 120 kg of ethyl orthosilicate, add 50 kg of ethanol and 30 kg of water, stir and mix, add 2 kg of ammonium hydroxide, stir and disperse thoroughly, add 64 kg of tert-butyl glycidyl carbonate, mix and heat in a water bath at 30°C for 22 hours to form a sol;

[0065] (2) Add the same amount of xylene as in Preparation Example 1 and the sol in step (1) and stir to obtain a mixed solution, put 80 kg of sintered mullite into the mixed solution and immerse for 60 minutes, filter, remove and dry at 80°C to obtain modified sintered mullite. Xylene is used as a solvent and the amount added is based on the amount that can fully dissolve the raw materials. The particle size of the sintered mullite is 2-3 mm.

[0066] Example

[0067] Example 1

[0068] A 3D printed lightweight high-strength low-carbon cement-based material, the preparation of which includes the following steps:

[0069] (1) After weighing the raw materials, 60 kg of modified sintered mullite, 6.5 kg of mineral admixture, 8 kg of coral aggregate, 10 kg of zeolite, 70 kg of cement and 15 kg of clay were stirred and mixed to obtain a mixture;

[0070] (2) Add 75 kg of nanobubble water to the mixture while stirring, and continue stirring for 5 minutes after the water is added to obtain a 3D printed lightweight, high-strength, low-carbon cement-based material. The modified sintered mullite is prepared in Preparation Example 1, and the mineral admixture is obtained by mixing microsilica powder and diatomaceous earth in a weight ratio of 2:1.

[0071] Example 2

[0072] A 3D printed lightweight high-strength low-carbon cement-based material, the preparation of which includes the following steps:

[0073] (1) After weighing the raw materials, 50 kg of modified sintered mullite, 8 kg of mineral admixture, 12 kg of coral aggregate, 8 kg of zeolite, 80 kg of cement and 20 kg of clay were stirred and mixed to obtain a mixture;

[0074] (2) Add 60 kg of nanobubble water to the mixture while stirring, and continue stirring for 5 minutes after the water is added to obtain a 3D printed lightweight, high-strength, low-carbon cement-based material. The modified sintered mullite is prepared in Preparation Example 3, and the mineral admixture is obtained by mixing microsilica powder and diatomaceous earth in a weight ratio of 1:2.

[0075] Example 3

[0076] (1) After weighing the raw materials, 70 kg of modified sintered mullite, 5 kg of mineral admixture, 10 kg of coral aggregate, 9 kg of zeolite, 60 kg of cement and 10 kg of clay were stirred and mixed to obtain a mixture;

[0077] (2) Add 65 kg of nanobubble water to the mixture while stirring, and continue stirring for 5 minutes after the water is added to obtain a 3D printed lightweight, high-strength, low-carbon cement-based material. The modified sintered mullite is prepared in Preparation Example 2, and the mineral admixture is obtained by mixing microsilica powder and diatomaceous earth in a weight ratio of 1:1.

[0078] Embodiment 4-7

[0079] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 1 in that the modified sintered mullite is prepared by Preparation Examples 4-7 respectively.

[0080] Example 8

[0081] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 1 in that 12.5 kg of water-based epoxy resin is also added in this embodiment, and specifically includes the following steps:

[0082] (1) After weighing all the raw materials, 60 kg of modified sintered mullite and 12.5 kg of waterborne epoxy resin were mixed and stirred, and then 6.5 kg of mineral admixture, 8 kg of coral aggregate, 10 kg of zeolite, 70 kg of cement and 15 kg of clay were added and stirred to obtain a mixture;

[0083] (2) Add 75 kg of nanobubble water to the mixture while stirring, and continue stirring for 5 minutes after the water is added to obtain a 3D printed lightweight, high-strength, low-carbon cement-based material. The modified sintered mullite is prepared in Preparation Example 1, and the mineral admixture is obtained by mixing microsilica powder and diatomaceous earth in a weight ratio of 2:1.

[0084] Example 9

[0085] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 8 in that 10 kg of water-based epoxy resin is also added in this example.

[0086] Example 10

[0087] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 8 in that 15 kg of water-based epoxy resin is also added in this example. Comparative Example

[0088] Comparative Example 1

[0089] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 1 in that unmodified sintered mullite is added in this comparative example and replaced with an equal amount of cement.

[0090] Comparative Example 2

[0091] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 1 in that the modified sintered mullite used in this comparative example is prepared by Comparative Preparation Example 1.

[0092] Comparative Example 3

[0093] A 3D printed lightweight, high-strength, low-carbon cement-based material, which is different from Example 1 in that an equal amount of ordinary water is used to replace nano bubble water in this comparative example.

[0094] Performance testing

[0095] Test methods

[0096] The cement-based materials prepared in the embodiments and comparative examples were injected into a machine to make corresponding test blocks, which were placed in a natural laboratory environment for 24 hours and then cured for 7 days under standard curing conditions for testing.

[0097] Compressive strength: A 100mm×100mm×100mm cubic specimen is used with a loading rate of 1MPa / s. The compressive strength of the specimen at room temperature is tested in accordance with GB / T17671-2021 "Test method for strength of cement mortar";

[0098] Fluidity test: Before the test according to GB / T 2419-2005 "Determination of fluidity of cement mortar", use a wet towel to moisten the truncated cone round mold, tamping rod, springboard and other tools that come into contact with the printing material. Place the truncated cone round mold at the center of the springboard, inject the printing material and tamp it, then scrape the top surface of the material flat. After scraping, lift the round mold at a uniform speed along the vertical direction of the springboard. Turn on the springboard and let it jump 25 times, then record the expansion diameter of the printing material slurry in the perpendicular direction to each other, and calculate the average value as the fluidity, accurate to 1mm;

[0099] Apparent density: Tested in accordance with GB / T 208-2014 "Standard for Test Methods of Mechanical Properties of Concrete";

[0100] Durability test: According to the quick freezing method in GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the frost resistance of the sample is tested. During the freeze-thaw cycle, the freezing temperature and melting temperature of the sample are -20℃--15℃ and 6℃-8℃ respectively. The freeze-thaw cycle lasts for 4 hours and is repeated 20 times. After the test, the compressive strength is tested.

[0101] Table 1 Experimental test results

[0102]

[0103] Combining Examples 1-3 and Comparative Examples 1-2 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than Comparative Examples 1-2, indicating that the use of hydrophobic materials to modify sintered mullite is beneficial to improving the disadvantages of its porous structure, effectively preventing the damage of moisture or unfavorable components in cement-based materials to the aggregate structure, and at the same time, the addition of acrylic resin can improve the compatibility of aggregates with other raw materials in cement-based materials, form a stronger chemical bond with the cement matrix, and improve the interfacial bonding strength of porous materials, thereby further improving the compressive strength of cement-based materials. At the same time, it can also be seen from Example 1 and Comparative Example 1 that the addition of modified mullite can effectively reduce the deadweight load of the material and achieve lightweight.

[0104] Combining Examples 1-3 with Comparative Example 3 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3, indicating that the addition of nano bubble water can further improve the microstructure of cement-based materials, effectively fill pores, inhibit crack generation, and further enhance the compressive properties of the material.

[0105] Combining Example 1 with Examples 4-5 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Examples 4-5, indicating that the addition of 2-butanone is beneficial to further improve the connection tightness between the modified sintered mullite surface layer coating and the mullite, and its antifreeze performance and durability are better.

[0106] Combining Example 1 with Examples 6-7 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Examples 6-7, indicating that the selection of sintered mullite particle size affects the performance of cement-based materials. Selecting mullite with a particle size between 2-3 mm provides good strength support for cement-based materials while being beneficial to their subsequent modification. The modified material can achieve uniform wrapping of mullite, improve uniformity, and thus improve the compressive strength of the material.

[0107] Combining Example 1 with Examples 8-10 and Table 1, it can be seen that the experimental data of Examples 8-10 are better than those of Example 1, indicating that the addition of water-based epoxy resin can, on the one hand, strengthen the bonding strength between the aggregate and the cement matrix, and on the other hand, react with the acrylic resin on the surface of the aggregate to form a network structure, thereby improving the strength of the cement-based material.

[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A 3D printed lightweight, high-strength, low-carbon cement-based material, characterized in that: The composition comprises the following raw materials in parts by weight: 50-70 parts of modified sintered mullite, 5-8 parts of mineral admixture, 8-12 parts of coral aggregate, 8-10 parts of zeolite, 60-80 parts of cement, 10-20 parts of clay, and 60-75 parts of nano bubble water, wherein the modified sintered mullite is obtained by being wrapped and modified by a hydrophobic material; the preparation of the modified sintered mullite specifically includes the following steps: (1) Add ethanol and water to ethyl orthosilicate and stir to mix, add ammonium hydroxide and stir to disperse, add tert-butyl glycidyl carbonate and mix, keep in a water bath at 30°C and allow to react for 18-24 hours; (2) placing an acrylic resin in xylene, heating and stirring until the acrylic resin is dissolved, adding the sol prepared in step (1) and continuing to stir and mix to obtain a mixed solution, placing the sintered mullite in the mixed solution, filtering, removing, drying and curing at 60-80°C to obtain the modified sintered mullite; In the step (2), 2-butanone is added dropwise after the sintered mullite is added into the mixed solution, and the weight ratio of the 2-butanone to the sintered mullite is 0.2-0.4:

1.

2. A 3D printed lightweight, high-strength, low-carbon cement-based material according to claim 1, characterized in that: In the preparation process, the weight ratio of ethyl orthosilicate, tert-butyl glycidyl carbonate, acrylic resin and sintered mullite is 3-4: 0.8:4.5-6.2:2。 3. A 3D printed lightweight, high-strength, low-carbon cement-based material according to claim 1, characterized in that: The particle size of the sintered mullite is between 2 and 3 mm.

4. A 3D printed lightweight, high-strength, low-carbon cement-based material according to claim 1, characterized in that: The mineral admixture is obtained by mixing microsilica powder and diatomaceous earth in any weight ratio.

5. A 3D printed lightweight, high-strength, low-carbon cement-based material according to claim 1, characterized in that: The raw materials also include 10-15 parts of water-based epoxy resin.

6. A method for preparing a 3D printed lightweight, high-strength, low-carbon cement-based material according to any one of claims 1-5, characterized in that: The steps include: (1) After weighing the raw materials, the modified sintered mullite, mineral admixture, coral aggregate, zeolite, cement and clay are stirred and mixed to obtain a mixture; (2) Adding nanobubble water to the mixture and performing secondary stirring to obtain a 3D printed lightweight, high-strength, low-carbon cement-based material.

Citation Information

Patent Citations

  • High-performance glycidyl tertiary carboxylic ester modified polysiloxane resin and preparation method thereof

    CN111234134A

  • Construction waste recycled fine aggregate surface modification method, concrete and application

    CN112876117A

  • Concrete as well as preparation method and application thereof

    CN113968709A

  • Lightweight concrete with low thermal conductivity

    CN113998942A

  • Recycled coral aggregate concrete suitable for island engineering and preparation method of recycled coral aggregate concrete

    CN117263616A